Implementing Various Strategies in Teaching English through Literature in Islamic Boarding School - Saputra, Untung Pararean Adjie; Rusafi, Wirda Farfaza Nabila Rusafi; Rohmana, Wahyu Indah Mala (English Education Postgraduate Program, Universitas Negeri Manado, 2024)
The study